PROFILING RARE BOTANICAL COMPOUNDS THROUGH GAS CHROMATOGRAPHY–MASS SPECTROMETRY: UNLOCKING NEW POTENTIAL IN NATURAL COSMETICS - LAKSHMI SHREE N; SUCHI MODI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study explores the chemical composition and cosmetic potential of four aromatic plants-Clove (Syzygium aromaticum), Patchouli (Pogostemon cablin), Bay Leaf (Cinnamomum tamala), and Galangal (Alpinia galanga)-using Gas chromatography–mass spectrometry (GC-MS) analysis and in vitro biological assays. Methods: Ethanol extracts of authenticated, herbarium-archived plant materials were prepared through Soxhlet extraction. GC-MS was used to identify phytochemicals in each extract. Antimicrobial activity was assessed against Klebsiella pneumoniae, Streptococcus mutans, and Candida albicans using the agar well diffusion method. Antioxidant activity was measured using the 2,2-diphenyl-1-picrylhydrazyl assay, while anti-inflammatory potential was evaluated by inhibiting protein denaturation. Results were analyzed statistically using one-way analysis of variance, with p<0.05 considered statistically significant. Results: Patchouli showed strong antimicrobial action with a 22.3±0.7 mm inhibition zone against S. mutans, while Clove inhibited K. pneumoniae with a zone of 19.8±1.2 mm. Galangal demonstrated notable anti-inflammatory activity with 74.6%±2.1% inhibition in the albumin denaturation test. Bay leaf extract had strong antioxidant activity with an IC50 of 43.2 μg/mL. GC-MS analysis revealed bioactive and rare compounds such as azulene, 1′-acetoxychavicol acetate, and elemicin, each with potential cosmetic value. Conclusion: The presence of multifunctional phytochemicals across these botanicals highlights their value in natural skincare development. With proven antioxidant, antimicrobial, and anti-inflammatory properties, these authenticated extracts offer promising clean-label ingredients for innovative, plant-based cosmetic formulations.